Jejunal diverticulitis: Things to know to prevent diagnostic mistake - Giuffrida, Mario; Perrone, Gennaro; Di Saverio, Salomone; Annicchiarico, Alfredo; Pattonieri, Vittoria; Bonati, Elena; Tarasconi, Antonio; Catena, Fausto (Acta Biomedica Atenei Parmensis, 2021)
We report a peculiar case of jejunal diverticulitis in 54-year-old female. Since hospital admission, a colonic diverticulitis was suspected. CT scan of the abdomen showed multiple fluid collections with free intraperitoneal extraluminal air, suggesting bowel perforation. A complicated acute diverticulitis of the colon was suspected but intraoperatively, a perforated acute diverticulitis of jejunum was detected. The aim of this work is to evidence the key role of CT scan of the abdomen in differential diagnosis of unfrequently pathological entities, such as jejunal diverticulitis, to prevent diagnostic mistakes.